Flux-Switching Permanent Magnet Machines: A Review of Opportunities and Challenges-Part I: Fundamentals and Topologies - Chen, Hao; EL-Refaie, Ayman M.; Demerdash, Nabeel A. O. (IEEE transactions on energy conversion, 2020)
Flux-switching permanent magnet (FSPM) machines have been gaining interest over the last few decades. This is due to the several advantages that this type of machines provides. These advantages include high torque density due to the flux-focusing effects, favorable thermal management due to the location of PMs on the stator, passive and hence robust rotor structure which is suitable for high-speed applications, etc. The two-part companion articles are going to provide a comprehensive analysis of FSPM machines in terms of opportunities and challenges. In the first part of these two-part series, it covers the principle theory, computation methods, various topologies of FSPM machines, and the comparison with other PM machines. Meanwhile, the basic performance characteristics and design requirements, viz. torque density, over-load torque capability, flux-weakening capability, fault-tolerance capability, as well as the latest development, are also provided.